The typology on subjectivity of re-socialization barriers among retired footballers - Wangsung Myung; Kwangho Park; Kyunghwan Jung (Korea Institute of Sport Science, 2020)
Purpose The purpose of this study is to classify the subjectivity of re-socialization barriers among retired footballers. Methods Q methodology was conducted to identify constraint factors contributing to social adjustment and reemployment perceived by 28 P-samples. Results Re-socialization barriers were classified as 'Type I: Internal-constraint', 'Type II: External-constraint', 'Type III: Internal-conflict', and 'Type IV: External-conflict'. These types provided a variety of academic and practical discussions, depending on where the barriers are taken from (internal and external) and what depends on them (objective conditions and subjective ideas). Conclusions This study focused on the subjective structure of retired footballers and complemented traditional methodology focusing on hypothesis testing. Therefore, each type found in this study provides useful information not only in follow-up study on retired athletes, but also in policy-making decision such as support projects.